2021
DOI: 10.3390/rs13245015
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Aware Neural Network for Semantic Segmentation of Multi-Resolution Remote Sensing Images

Abstract: Assigning geospatial objects with specific categories at the pixel level is a fundamental task in remote sensing image analysis. Along with the rapid development of sensor technologies, remotely sensed images can be captured at multiple spatial resolutions (MSR) with information content manifested at different scales. Extracting information from these MSR images represents huge opportunities for enhanced feature representation and characterisation. However, MSR images suffer from two critical issues: (1) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Directly from an architecture perspective, Mitton et al [48] designs the rotation equivariant convolutional neural network model to efficiently perform the deforestation segmentation. Moreover, through the designed densely connected feature network and the spatial feature recalibration module, the SaNet [49] successfully extracts the scale-aware feature representation to enhance the performance of aerial image semantic segmentation. Similarly, Sci-Net [50] leverages UNet hierarchical representation and dense atrous spatial pyramid pooling to achieve scaleinvariant building segmentation from aerial imagery.…”
Section: A Aerial Image Semantic Segmentationmentioning
confidence: 99%
“…Directly from an architecture perspective, Mitton et al [48] designs the rotation equivariant convolutional neural network model to efficiently perform the deforestation segmentation. Moreover, through the designed densely connected feature network and the spatial feature recalibration module, the SaNet [49] successfully extracts the scale-aware feature representation to enhance the performance of aerial image semantic segmentation. Similarly, Sci-Net [50] leverages UNet hierarchical representation and dense atrous spatial pyramid pooling to achieve scaleinvariant building segmentation from aerial imagery.…”
Section: A Aerial Image Semantic Segmentationmentioning
confidence: 99%
“…ResNet's [40] complex residual modules give it a strong feature extraction capability. Numerous studies [2,13,41] have shown that a pre-trained ResNet backbone performs well in segmentation tasks. ResNet is used as an encoder in the suggested framework, albeit without fully connected (FC) layers.…”
Section: Deep Residual Encodermentioning
confidence: 99%
“…The semantic segmentation of HRRSIs is to categorize each pixel in remote sensing (RS) images. With the rapid development of RS acquisition technology, semantic segmentation applications of HRRSIs have become more widespread [1][2][3]. The semantic segmentation's robustness and the generalization ability of RS images are crucial for applications such as mapping, land use, earth observation, and land cover.…”
Section: Introductionmentioning
confidence: 99%
“…The framework consists of a double branch, partly used to suppress the large-scale background and partly used to activate the features of small objects. Some recent methods [5,27,28] try to incorporate modules that are effective in the field of general segmentation into remote sensing image segmentation networks, such as the well-known transformer or attention mechanisms, which are effective in improving the accuracy of the networks to some extent. However, these methods mainly target special application scenarios and are not effective in solving problems of semantic segmentation for high-resolution remote sensing images, such as multi-scale variation of objects and loss of foreground details.…”
Section: Semantic Segmentation In Remote Sensingmentioning
confidence: 99%